Studies on Blue Discolouration i Canned Body Meat of Crab (Scylla serrata) - VIJAYAN, P K; BALACHANDRAN, K K (Fishery Technology, 2017)
Blue discolouration met with in the canned body meat of crab (Scylla serrata) wasdue to copper content exceeding 1.8 to 2.0 mg/100g on dry weight basis. leeding the cleaned carcasses of crab thoroughly in running water brought down the copper content below this level and blue discolouration prevented. Addition of copper ions to the thoroughly bled crab meat to raise the copper content above this level caused discolouration. The incidence of blue discolouration was independent of the freshness of the animals used. Citric acid in high concentration prevented blueing to some extent, but is not advisable as texture and flavour were adversely affected.